Breast cancer-specific mutations in CK1ε inhibit Wnt/β-catenin and activate the Wnt/Rac1/JNK and NFAT pathways to decrease cell adhesion and promote cell migration - Foldynová-Trantírková, Silvie (BioMed Central, 2010)
INTRODUCTION: Breast cancer is one of the most common types of cancer in women. One of the genes that were found mutated in breast cancer is casein kinase 1 epsilon (CK1ε). Because CK1ε is a crucial regulator of the Wnt signaling cascades, we determined how these CK1ε mutations interfere with the Wnt pathway and affect the behavior of epithelial breast cancer cell lines. METHODS: We performed in silico modeling of various mutations and analyzed the kinase activity of the CK1ε mutants both in vitro and in vivo. Furthermore, we used reporter and small GTPase assays to identify how mutation of CK1ε affects different branches of the Wnt signaling pathway. Based on these results, we employed cell adhesion and cell migration assays in MCF7 cells to demonstrate a crucial role for CK1ε in these processes. RESULTS: In silico modeling and in vivo data showed that autophosphorylation at Thr 44, a site adjacent to the breast cancer point mutations in the N-terminal lobe of human CK1ε, is involved in positive regulation of the CK1ε activity. Our data further demonstrate that, in mammalian cells, mutated forms of CK1ε failed to affect the intracellular localization and phosphorylation of Dvl2; we were able to demonstrate that CK1ε mutants were unable to enhance Dvl-induced TCF/LEF-mediated transcription, that CK1ε mutants acted as loss-of-function in the Wnt/β-catenin pathway, and that CK1ε mutants activated the noncanonical Wnt/Rac-1 and NFAT pathways, similar to pharmacological inhibitors of CK1. In line with these findings, inhibition of CK1 promoted cell migration as well as decreased cell adhesion and E-cadherin expression in the breast cancer-derived cell line MCF7. CONCLUSIONS: In summary, these data suggest that the mutations of CK1ε found in breast cancer can suppress Wnt/β-catenin as well as promote the Wnt/Rac-1/JNK and Wnt/NFAT pathways, thus contributing to breast cancer development via effects on cell adhesion and migration. In terms of molecular mechanism, our data indicate that the breast cancer point mutations in the N-terminal lobe of CK1ε, which are correlated with decreased phosphorylation activities of mutated forms of CK1ε both in vitro and in vivo, interfere with positive autophosphorylation at Thr 44.